PERCEPTION OF THE AVAILABILITY AND PROVISION OF CAREER COUNSELLING SERVICE IN COLLEGE (Contemporary Journal of Social Science Review, 2025)
This study examines student and staff perceptions of access to and the availability of career counseling services in government colleges in rural areas. The aim was to investigate the level of service availability, stakeholder awareness, and the effectiveness of current counseling mechanisms, since it is essential for students to have informed and educated decisions in both academic and professional choices through counseling sessions. A structured questionnaire was developed and used to conduct a quantitative research study by administering it to 200 respondents, including 150 students and 50 staff members at selected government colleges in rural regions. The results showed that both students and staff highly value career counseling as a way to guide students toward the most suitable educational and career options. However, the data also revealed a lack of formally organized or structured counseling services and trained professionals in these institutions. Inferential statistical analysis indicated a significant difference in perceptions based on gender and role (student or staff), with staff generally showing a more positive attitude toward service provision than students. To address these issues and better support students’ career planning, the research recommends appointing professional career counselors, developing counseling infrastructure, holding awareness sessions, and integrating career guidance into the academic system, ensuring rural students receive adequate support for their future planning. This study contributes new insights into how policies and their implementation relate within the context of rural education in Pakistan.